Morphological Evidence for a Unique Neuromuscular Functional Unit of the Human Vocalis Muscle - Tracicaru, Rareș Vasile; Bräuer, Lars; Döllinger, Michael; Schicht, Martin; Tillmann, Bernhard; Hînganu, Delia; Hristian, Liliana; Hînganu, Marius Valeriu; Paulsen, Friedrich (International Journal of Molecular Sciences, 2024)
Human vocalization is a complex process that is still only partially understood. Previous studies have suggested the possibility of a localized neuromuscular network of the larynx. Here we investigate this structure in human dissection specimens using multiple immunofluorescence and transmission electron microscopy (TEM). In the area of the pars interna of the thyroarytenoid muscle, muscle fibers are present that are clearly differentiated from skeletal or cardiac muscle cells and show an intermediate ultrastructure. In addition, intramuscular neurons are present that are detectable by both electron and fluorescence microscopy and may have a sensory function in a local neuronal network. Also, several types of sensory and motor synapses are detectable and distributed throughout the pars interna of the thyroarytenoid muscle, with multisynaptic muscle fibers being a common feature. These findings suggest the existence of a previously unrecognized type of muscle fiber coupled to an intramuscular neuronal network, the presence of which could explain functional peculiarities at the laryngeal level.
CRIS-Team Scopus Importer:2025-02-04
Keywords: electron microscopy; immunofluorescence; laryngeal muscles; laryngeal nerves; larynx; neural network; neurolaryngology; neuromuscular junctions; synapses; voice formation